Class dismissed : why we cannot teach or learn our way out of inequality - Marsh, John, 1975- (Monthly Review Press, 2011)
"In Class Dismissed, John Marsh debunks a myth cherished by journalists, politicians, and economists: that growing poverty and inequality in the United States can be solved through education. Using sophisticated analysis combined with personal experience in the classroom, Marsh not only shows that education has little impact on poverty and inequality, but that our mistaken beliefs actively shape the way we structure our schools and what we teach in them. Rather than focus attention on the hierarchy of jobs and power--where most jobs require relatively little education, and the poor enjoy very little political power--money is funneled into educational endeavors that ultimately do nothing to challenge established social structures, and in fact reinforce them. And when educational programs prove ineffective at reducing inequality, the ones whom these programs were intended to help end up blaming themselves. Marsh's struggle to grasp the connection between education, poverty, and inequality is both powerful and poignant"--Provided by publisher